2017
DOI: 10.7150/ijms.18896
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and determination of four potential antimicrobial components from Pseudomonas aeruginosa extracts

Abstract: Background: Pseudomonas aeruginosa can cause disease and also can be isolated from the skin of healthy people. Additionally, it exhibits certain antimicrobial effects against other microorganisms.Methods: We collected 60 strains of P. aeruginosa and screened their antimicrobial effects against Staphylococcus aureus (ATCC 25923) using the filter paper-disk method, the cross-streaking method and the co-culture method and then evaluated the antimicrobial activity of the chloroform-isolated S. aureus extracts agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
3
9
0
Order By: Relevance
“…Bandara, Yau [34] reported that the interaction among P. aeruginosa and 5 non-C. albicans Candida species was variable and species-specific; a finding that is in agreement with our results. Also, in keeping with our observations, variation in the effect of the tested P. aeruginosa on the tested Candida species was reported by Xu, Zeng [10]. In particular, some P. aeruginosa exhibited high antifungal activity and some showed partial or no activity against the tested Candida spp.…”
Section: Plos Onesupporting
confidence: 91%
See 2 more Smart Citations
“…Bandara, Yau [34] reported that the interaction among P. aeruginosa and 5 non-C. albicans Candida species was variable and species-specific; a finding that is in agreement with our results. Also, in keeping with our observations, variation in the effect of the tested P. aeruginosa on the tested Candida species was reported by Xu, Zeng [10]. In particular, some P. aeruginosa exhibited high antifungal activity and some showed partial or no activity against the tested Candida spp.…”
Section: Plos Onesupporting
confidence: 91%
“…Also, in keeping with our observations, variation in the effect of the tested P . aeruginosa on the tested Candida species was reported by Xu, Zeng [ 10 ]. In particular, some P .…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…These findings are in concordance with studies that have shown P. aeruginosa to produce antimicrobial exoproducts effective against S. aureus. 24,[32][33][34] The layered woundlike growth medium contained laked horse blood, cattle serum, and peptone, which is similar to wound-simulating media used in several studies. 20,24,25 According to Thaarup and Bjarnsholt, a suitable medium simulating wound fluid should consist of a meat-based broth combined with mammal serum and red blood cells, because the wound bed is recognized to contain mainly damaged host tissue, plasma and red blood cells.…”
Section: Biofilm Model Developmentmentioning
confidence: 99%
“…The discovery of penicillin in 1928 revealed that microorganisms may contribute to known existing issues, due to the abundant bioactive substances produced within their cells (L.-Q. Xu et al, 2017). Some pathogens have been shown to develop antimicrobial-resistant properties, leading to increased morbidity, mortality, and healthcare costs (Pratiwi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%